Transforming mentorship in STEM by training scientists to be better leaders. Issue 20 (2nd October 2018) - Hund, Amanda K.; Churchill, Amber C.; Faist, Akasha M.; Havrilla, Caroline A.; Love Stowell, Sierra M.; McCreery, Helen F.; Ng, Julienne; Pinzone, Cheryl A.; Scordato, Elizabeth S. C.
Abstract: Effective mentoring is a key component of academic and career success that contributes to overall measures of productivity. Mentoring relationships also play an important role in mental health and in recruiting and retaining students from groups underrepresented in STEM fields. Despite these clear and measurable benefits, faculty generally do not receive mentorship training, and feedback mechanisms and assessment to improve mentoring in academia are limited. Ineffective mentoring can negatively impact students, faculty, departments, and institutions via decreased productivity, increased stress, and the loss of valuable research products and talented personnel. Thus, there are clear incentives to invest in and implement formal training to improve mentorship in STEM fields. Here, we outline the unique challenges of mentoring in academia and present results from a survey of STEM scientists that support both the need and desire for more formal mentorship training. Using survey results and the primary literature, we identify common behaviors of effective mentors and outline a set of mentorship best practices. We argue that these best practices, as well as the key qualities of flexibility, communication, and trust, are skills that can be taught to prospective and current faculty. We present a model and resources for mentorship training based on our research, which we successfully implemented at the University of Colorado, Boulder, with graduate students and postdocs. We conclude that such training is an important and cost‐effective step toward improving mentorship in STEM fields. Abstract : Effective mentoring is a key component to success in STEM fields and plays an important role in mental health and in retaining diverse students, yet scientists generally do not receive training in mentorship skills. We outline the unique challenges of mentoring in academia, present results from a survey of STEM scientists that supports the need for more mentorship training, identify common qualities of effective mentors, and outline a set of mentorship best practices. Finally, we provide a model and resources for mentorship training that we have successfully implemented.